The thrill of chance: Psychophysiological responses in loot boxes and simulated slot machines - Francisco J. Sanmartín; Judith Velasco; Fátima Cuadrado; Juan A. Moriana (Computers in Human Behavior Reports)
Loot boxes (LBs) are microtransactions within video games that offer players the opportunity to acquire virtual items randomly. LBs shared structural and psychological features with gambling, especially slot machines. However, one potential shared feature that has been scarcely explored in LBs, is the level of arousal experienced by players. This study explores changes in electrodermal activity (EDA), heart rate (HR) and respiratory rate (RR) during the opening of LBs in FIFA and during simulated slot machine spin in gamblers (n = 14, M = 19.93 years), LB users (n = 13, M = 19.62 years) and a control group (n = 13, M = 21.92 years). Additionally, the study aimed to compare psychophysiological activation levels produced by both dynamics in each group. Results indicated that both gamblers and LB users showed increased EDA during LB opening and slot machine spins, while HR or RR did not exhibit significant changes. The control group showed increased EDA during the slot machine spin, with no changes during LB opening or in other psychophysiological measures. The comparison between LB opening and slot machine spin revealed similar levels of psychophysiological activation for gamblers and LB users. These findings suggest a potential link between gambling and LBs, which could inform the development of policies for safer gaming environments.